Insulin and IGF-1 improve mitochondrial function in a PI-3K/Akt-dependent manner and reduce mitochondrial generation of reactive oxygen species in Huntington’s disease knock-in striatal cells - Ribeiro, Márcio (2014)
Akt, protein kinase B; ARE, antioxidant response element; Erk, extracellular signal-regulated kinase; CBP, CREB-binding protein; CREB, cAMP response-element (CRE) binding protein; CDK, cyclin-dependent kinase; DHE, dihydroethidium; Drp1, dynamin-related protein 1 or dynamin 1-like (DNM1L); GCL, glutamate-cysteine ligase; GCLc, glutamate-cysteine catalytic subunit; GPx, glutathione peroxidase; GSH, glutathione, reduced form; GSSG, glutathione oxidized form; IGF-1, Insulin-like growth factor 1; IGF1R, insulin-like growth factor 1 receptor; IR, insulin receptor; IRS, insulin receptor substrate; H2DCFDA, 2′,7′-dichlorodihydrofluorescein diacetate; HKII, hexokinase type II; HD, Huntington’s disease; HO-1, heme oxygenase; Hsp60, heat shock 60 kDa protein 1 (chaperonin); mHtt, mutant huntingtin; mtDNA, mitochondrial DNA; MT-COII, mitochondrial-encoded cytochrome c oxidase II; mTOR, mammalian target of rapamycin; NDUFS3, NADH dehydrogenase (ubiquinone) Fe–S protein 3, 30 kDa (NADH-coenzyme Q reductase); NQO1, NAD(P)H dehydrogenase [quinone] 1; Nrf2, nuclear factor (erythroid-derived 2)-like 2; PI-3K, phosphatidylinositol 3-kinase; PGC-1α, peroxisome proliferator-activated receptor-γ coactivator 1α; ROS, reactive oxygen species; SDHA, succinate dehydrogenase complex, subunit A, flavoprotein (Fp); SOD, superoxide dismutase; Tfam, transcription factor A, mitochondrial; TMRM, tetramethylrhodamine methyl ester; Tom20, translocase of outer mitochondrial membrane 20 homolog (yeast); Tom40, translocase of outer mitochondrial membrane 40 homolog (yeast).